Predicting the coefficient of permeability of soils based on grain size analysis - ASHIL V. S; Drisya J; Haritha V. P; Rose Antony; Er. Renuka Kumari J (Guide) (Tavanur 2009 Department of Land and Water Resources and Conservation Engineering)
Predicting the coefficient of permeability of soils based on grain size analysis
Predicting the coefficient of permeability of soils based on grain size analysis